Florid cystitis glandularis: a case report - Najman, Ahmad Farhan; Mohamed Sufian, Mohamad 'Arif Rukaini; Abdul Rasid, Muhammad Hafiz; Azmi, Muhamad Zulhilmi; Abu Bakar, Intan Bazilah; Kamarulzaman, Mohd Nazli (OASK Publishers, 2025)
Introduction • Cystitis glandularis is a critical pathological diagnosis with a presentation that closely resembles bladder tumors, potentially causing concern for clinicians. • A cautious and thorough approach is crucial to prevent delayed management, as it can be mistaken for aggressive tumors. • Only a few cases of cystitis glandularis presenting as urinary bladder masses have been reported in the literature. Case Report • We recently encountered a young 31 years old gentleman who • experienced recurring lower urinary tract symptoms and was initially treated for recurrent urinary tract infections. • However, no palpable mass or infection evidence was found after a comprehensive clinical and biochemical examination. • An KUB ultrasound performed and revealed a vascularized lesion in the bladder (Figure 1 and 2).